A valorização do festival do Cupuçai na Comunidade de Santa Maria no Municipio de Santarém-Pará - MARCIÃO, Aldenora Rodrigues (Universidade Federal do Oeste do Pará, 2024)
His paper analyzes the importance of popular culture for the development of a community. The theme was: The cupuçai festival in the community of Santa Maria in the municipality of Santarém-Pará. Aiming to know about the importance of cultural manifestations for the identity of a people; to identify the different perceptions about the concept of the Cupuçai Festival in the community of Santa Maria and also to reflect on the benefits for the families with the accomplishment of the event and how they manage to generate income to maintain their tradition. We opted for field research, observing their beliefs and customs, talking with residents and sympathizers of the event, as well as an interview with 10 closed questions to the old residents and community leaders. In this research we opted for the qualitative method, which aims to analyze accurately the data collected. Considering the results, it is noticed that the manifestations and popular expressions that hold the context is of paramount importance for the reinforcement, evaluation and incentive to the development of the region.